Featured Cover. Issue 2 (22nd March 2023) - Abreu‐Placeres, Ninoska; Newton, Jonathon Tim; Avila, Viviana; Garrido, Luis E.; Jácome‐Liévano, Sofia; Pitts, Nigel B.; Ekstrand, Kim R.; Ochoa, Emilia M.; Martignon, Stefania
Abstract : The cover image is based on the Original Article How do dental practitioners, educators and students diagnose and manage caries risk and caries lesions? A COM‐B analysis by Ninoska Abreu‐Placeres et al., https://doi.org/10.1111/cdoe.12735 .